Bioaugmentation with the sulfur oxidizing Thauera sp. HDD1 for shortening the startup time in the denitrifying sulfide removal process. (September 2019) - Zhao, Youkang; Huang, Cong; Ma, Xiaodan; Chen, Fan; Liang, Bin; Wang, Aijie
Abstract: The denitrifying sulfide removal (DSR) process supplied an effective method to recovery S 0 and the removal of nitrate from wastewater. However, long startup time limited the application. This study presents an effective strategy of bioaugmentation with the sulfur oxidizing Thauera sp. HDD1 to reducing the startup time in the DSR process. In the bioaugmentation reactors, the removal efficiency of acetate and nitrate reached 87% and 91% on the 3 rd day, and S 0 generation in bioaugmentation reactor was rapidly improved to 97–144 mg/L. However, the treatment efficiency in the no-bioaugmentation reactor kept stable until day 33–38. Compared with the control, the startup time of DSR process shortened ~35 days. Thauera, Azoarcus, and Arcobacter were proven the core functional genera in the DSR process. Meanwhile, strain HDD1 colonized in bioaugmentation reactors and played an effective role of sulfide oxidization and denitrification during the startup time. Highlights: Inoculation of core functional bacteria (strain HDD1) shortened the startup time of DSR. Bioaugmentation improved the removal efficiency of acetate and nitrate on the 3rd day. High-throughput sequencing and qRT-PCR proved the colonization of strain HDD1.